Metformin as a novel organic foliar bio-stimulant to enhance peanut (Arachis hypogaea L.) growth and yield under drought stress conditions - Marwa A. Qotb; Ismail A. Abdelhamid; Nader R. Habashy; Abdel Rahman Mohammad Al Tawaha; Abdel Razzaq Al-Tawaha; Arun Karnwal; Tabarak Malik (BMC Plant Biology)
Abstract Background Drought stress significantly affects peanut (Arachis hypogaea L.) growth and yield, necessitating strategies to enhance crop resilience. This study evaluates the impact of foliar-applied Metformin, gibberellic acid (GA₃), and indole-3-acetic acid (IAA) at concentrations of 5.0, 7.5, and 10.0 mg L⁻1 under different irrigation regimes (100%, 80%, and 60% of the recommended irrigation rate). Methods A two-year field experiment was conducted under arid conditions to assess the effects of these treatments on plant growth, yield, photosynthetic pigments, nutrient uptake, and water use efficiency (WUE). Peanut plants were exposed to three irrigation levels (100%, 80%, and 60%), and foliar treatments were applied at specific growth stages. Photosynthetic parameters, including chlorophyll and carotenoid content, were measured alongside growth and yield attributes to determine treatment efficacy. Results The application of Metformin at 7.5 mg L⁻1 under 80% irrigation significantly improved plant height (76.9 cm), branch number (17.7 per plant), fresh weight (2928.5 kg acre⁻1), dry biomass (329.1 kg acre⁻1), and total seed yield (1593.9 kg acre⁻1) compared to other treatments. Additionally, water use efficiency (WUE) increased by 50.8% in plants treated with Metformin at 7.5 mg L⁻1 under 80% irrigation compared to untreated plants. The highest chlorophyll content (1.27 mg g⁻1 FW) and carotenoid levels (2.87 mg g⁻1 FW) were observed with Metformin at 7.5 mg L⁻1 under 100% irrigation, indicating improved photosynthetic performance. Conclusion Foliar application of Metformin at 7.5 mg L⁻1 under 80% irrigation effectively enhances peanut growth, yield, and WUE, providing a sustainable strategy to mitigate drought stress effects. This treatment balances crop productivity and water conservation, making it a viable approach for peanut cultivation in water-limited environments.